2023
DOI: 10.3390/microorganisms11020422
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Microbial Diversity with Age and Other Clinical Variables among Pediatric Chronic Rhinosinusitis (CRS) Patients

Abstract: Chronic rhinosinusitis (CRS) is a heterogenous disease that causes persistent paranasal sinus inflammation in children. Microorganisms are thought to contribute to the etiology and progression of CRS. Culture-independent microbiome analysis offers deeper insights into sinonasal microbial diversity and microbe–disease associations than culture-based methods. To date, CRS-related microbiome studies have mostly focused on the adult population, and only one study has characterized the pediatric CRS microbiome. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Finally, an open‐label randomized controlled trial assessing pediatric CRS with intranasal corticosteroid treatment leads to a greater increase in nasopharyngeal microbiome richness and a larger decrease in nasal Type 3 Innate Lymphoid Cell abundance 26 . These collective findings suggest pediatric CRS has distinct characteristics and behaviors when compared to adult CRS 27 …”
Section: Discussionmentioning
confidence: 96%
“…Finally, an open‐label randomized controlled trial assessing pediatric CRS with intranasal corticosteroid treatment leads to a greater increase in nasopharyngeal microbiome richness and a larger decrease in nasal Type 3 Innate Lymphoid Cell abundance 26 . These collective findings suggest pediatric CRS has distinct characteristics and behaviors when compared to adult CRS 27 …”
Section: Discussionmentioning
confidence: 96%
“…Alpha diversity studies also indicate an association between adenoid microbiome and different clinical statuses and medication effects. For example, authors have suggested a reduction in alpha diversity with nasal steroid use and changes in diversity with age [ 29 ]. Our findings, unfortunately, account for different topical medication use and we cannot corroborate these findings.…”
Section: Discussionmentioning
confidence: 99%